Structure et potentiel de développement du SIPAM réseau d'information pour le développement de l'aquaculture en Méditerranée - Lacroix D. (Aspects économiques de la production aquacole, 1995)
The Mediterranean sea is hosting about 150 million people, numerous industries and one third of the world tourism (117 million visitors in 1987). It represents a huge pressure for a nearly-closed, fragile and vulnerable sea. How can aquaculture find some space for development in a general context of increasing pollution, competition of activities on the seashore and also the will of wild preservation? The weakness of aquaculture is also a chance: it is the first victim of its own pollution and reacts as an alarm for environment quality. Therefore, aquaculture shows to be a favourable place for co-operation between all actors. The first need of this co-operation is information which has to be reliable, diversified and updated in order to feed analysis and enlighten decisions. Four priority topics have been selected by the fourteen member countries of MEDRAP Project (1982-1995). They have become in 1993 four specialized networks: Environment, Technology, Socio-economics and Information. SIPAM is the network specialized in information. It gathers nine countries and has just completed the experimental phase of the software allowing collection and exchange of international and national data about aquaculture in the Mediterranean. Its development is based first, on the numerous links that will be established with other networks and databanks (FAO, national institutes, regional similar networks) and second, in the improvement of the software by the creation of new specialized databases, whose elaboration would be realized in close co-operation with potential end-users (pathologists, lawyers, development planning agencies, etc.). This evolution is rich on synergies on scientific, technical and economical fields.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/05/17-19, Montpellier (France)